Essay and essayism between modernism and postmodernism - Zima, Peter V. (Primerjalna književnost, 2010)
The article is an attempt to show to what extent the essay, which is situated between philosophy and literature, is an anti-systematic genre open to individual experience and aiming at the particular phenomenon. Although this openness is a feature common to modernist and postmodern essayistic writing, developments in literature and philosophy show that modernist essayism (from Musil to Adorno) contained a utopian dimension which disappears in a postmodern constellation (from Robbe-Grillet and Fowles to Barthes) marked by a one-dimensional view of society. The question concerning an alternative social order is no longer raised in postmodern essayism.
Keywords: književnost; literature; philosophy; filozofija; literarni žanri; esej; modernizem; postmodernizem; utopija; partikularnost